Avifauna Diversity and Conservation Status of Majalgaon Reservoir, Maharashtra State, India - Maykar, Manisha B.; Pawar, R. T (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Majalgaon Reservoir, located in Beed district, Maharashtra, serves as a significant wetland ecosystem, providing habitat to a diverse range of avifaunal species. This study aims to document the diversity and ecological significance of the avifauna in and around the reservoir. The survey of avifauna was carried out for one year (January 2024 to december 2024). A total of 36 bird species were identified during the study. There are 23 families represented among the recorded bird species. The species belong to 1o different orders. The dominant family is Ardeidae with 5 species, including Little Egret, Cattle Egret, Large Egret, Grey Heron and Indian Pond Heron. This dominance indicates the importance of wetlands and aquatic habitats in supporting a diverse range of water birds in the reservoir area. Out of the 36 species, 34 are classified as Least Concern (LC), indicating that they are not currently facing significant threats. However, two species—the Oriental Darter and the Black-winged Pratincole are classified as Near Threatened (NT), meaning they are at risk of becoming vulnerable if existing threats persist. Additionally, several species, including the Black-winged Pratincole and the Rosy Starling, are migratory, emphasizing the importance of conserving their breeding and wintering habitats. The study underscores the importance of the Majalgaon Reservoir as a biodiversity hotspot and calls for the implementation of conservation measures to mitigate threats such as habitat degradation, water pollution, and human disturbances. This research provides baseline data for future studies and contributes to the understanding of wetland ecosystems in semi-arid regions, emphasizing the need for integrated management strategies to ensure the long-term sustainability of avifaunal diversity in the region.